House of bone and rain : a barrio noir - Iglesias, Gabino (Mulholland Books/Little, Brown and Company, 2024)
For childhood friends Gabe, Xavier, Tavo, Paul, and Bimbo, death has always been close. Hurricanes. Car accidents. Gang violence. Suicide. "Estamos rodeados de fantasmas" was Gabe's grandmother's refrain. We are surrounded by ghosts. But this time is different. Bimbo's mom has been shot dead. "We're gonna kill the guys who killed her," Bimbo swears. And they all agree. Feral with grief, Bimbo has become unrecognizable, taking no prisoners in his search for names. Soon, they learn Maria was gunned down by guys working for the drug kingpin of Puerto Rico. No one has ever gone up against him and survived. As the boys strategize, a storm gathers far from the coast. Hurricanes are known to carry evil spirits in their currents and bring them ashore, spirits which impose their own order. Blurring the boundaries between myth, mysticism, and the grim realities of our world, "House of Bone and Rain" is a harrowing coming of age story--a doomed tale of devotion, the afterlife of violence, and what rolls in on the tide. --